The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1002/hep.26191
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors and prevention of radioembolization-induced liver disease

Abstract: Radioembolization (RE)‐induced liver disease (REILD) has been defined as jaundice and ascites appearing 1 to 2 months after RE in the absence of tumor progression or bile duct occlusion. Our aims were to study the incidence of REILD in a large cohort of patients and the impact of a series of changes introduced in the processes of treatment design, activity calculation, and the routine use of ursodeoxycholic acid and low‐dose steroids (modified protocol). Between 2003 and 2011, 260 patients with liver tumors tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
178
0
10

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 242 publications
(209 citation statements)
references
References 26 publications
3
178
0
10
Order By: Relevance
“…In accordance to our results, Gil-Alzugaray [5] reported no relevant RILD in the treated patients with normal liver parenchyma, but in patients with cirrhosis or prior and subsequent chemotherapy.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In accordance to our results, Gil-Alzugaray [5] reported no relevant RILD in the treated patients with normal liver parenchyma, but in patients with cirrhosis or prior and subsequent chemotherapy.…”
Section: Discussionsupporting
confidence: 92%
“…These can be on the one hand complications b Fig. 2 due to the RE treatment [5,15,24,29,30] and on the other hand complications due to coil embolization associated with the therapy [1,19,25,28]. Peterson et al [24] performed a study in order to estimate the incidence of complications after 90 Y microsphere RE for unresectable hepatic tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneously, proinflammatory pathways are activated, resulting in endothelial injury with the activation of the coagulation cascade (57). Jaundice and ascites, in the absence of tumor progression or bile duct dilatation, are the main symptoms of radioembolization-induced liver disease (56,58). General risk factors for developing radioembolization-induced liver disease include prior chemotherapy, low tumor burden, high baseline bilirubin values, and cirrhotic liver disease (56,58).…”
Section: Clinical Outcome and Tumor Responsementioning
confidence: 99%
“…The use of SIRT is less likely in the situation of non-liver-dominant disease. In a cohort study of 260 patients, it was found that REILD only occurred in patients who had cirrhosis or who had been exposed to prolonged chemotherapy (50). The type of chemotherapeutic agent did not impact on the incidence of REILD.…”
Section: Rationale and Recommendationsmentioning
confidence: 95%